Finite-Time Synchronization of Input Delay Complex Networks via Non-fragile Controller. Issue 16 (November 2020) - He, Shenghuang; Wu, Yuanqing; Li, Yanzhou
Abstract: This paper investigates the finite-time synchronization problem of complex networks subject to input delay. The time-varying sampling is required to be aperiodic, which implies that the difference of any two continuous sampling instants does not exceed a given upper bound. Together with free-weighting matrix approach, a fresh Lyapunov functional is employed to establish a sufficient condition, solving the finite-time synchronization problem. Then, the synchronization of complex networks with input time-varying delay within a given time interval is considered. In order to solve such a problem, sufficient conditions are obtained based on non-fragile control protocol, the Lyapunov-Krasovskii stability theory (LKST) and integral inequality. The finite-time stability of complex networks in the presence of delay input delay can be achieved. At last, the smaller conservatism and the effectiveness of the obtain theoretical result is exhibited through some numerical simulations.